Über eine Verschärfung der Grenzwertsätze für die homogenen Markovschen Kette - Aleškevičienė-Džiugaitė, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене-Джюгайте. Об уточнении предельных теорем для однородных цепей Маркова A. Aleškevičienė-Džiugaitė. Homogeninių Markovo grandinių ribinių teoremų patikslinimo klausimu